META ANALYSIS OF THE EFFECT OF COOPERATIVE LEARNING MODELS ON STUDENT LEARNING OUTCOMES PHYSICS IN HIGH SCHOOL PHYSICS AND JUNIOR HIGH SCIENCE - Rizki Rizki; Yenni Darvina; - Desnita; Fanny Rahmatina Rahim (PILLAR OF PHYSICS EDUCATION, 2022)
The 2013 curriculum expects students to be directly involved in the learning process in order to achieve ideal learning outcomes.To achieve ideal learning outcomes, a learning strategy that may engage students in the learning process is needed, and one option is a cooperative learning strategy. Research on the cooperative model has been done by many previous researchers with the findings demonstrating that the cooperative learning strategy significantly affects the learning outcomes of understudies. The formulation of the research problem is how the effect of cooperative learning models on learning resultsof Physics and Science in terms of the level of the education unit, subject matter unit, cooperative learning type and research area. A meta-analysis was conducted utilizing a quantitative method to compile some of the findings of earlier investigations. From the data analysis carried out, the results showed that the impact of cooperative learning model on learning results of physics and science based on the level of the education unit is effectively use at the high school level with a summary effect size of 1.084 categorized as very high, based on the subject matter unit it is very influential on the magnetic electric material unit with a summary effect size of 1.516 categorized as very high , based on the type of effective cooperative learning used in the Team Games Tournaments type with a summary effect size of 1.380 categorized as very high and based on the research area it was influential in the South Kalimantan region with a summary effect size of 1.380 categorized as very high.